2015
DOI: 10.4103/0250-474x.164782
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eleven heavy metals in moringa oleifera lam. products

Abstract: Eleven heavy metals in various products of Moringa oleifera were analyzed to determine eleven heavy metals (Al, As, Cd, Cr, Cu, Fe, Pb, Mn, Hg, Ni, and Zn) using Inductively Coupled Plasma-Mass Spectrometry. The products of M. oleifera were purchased in Nakhon Pathom, Thailand. All products were digested with nitric acid solution before determining the concentrations of heavy metals. The recoveries of all heavy metals were found to be in the range of 99.89-103.05%. Several criteria such as linearity, limits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
0
22
1
Order By: Relevance
“…Allowing for differences in analytical method and likely inter-study variation in leaf maturity there are many broad similarities. For example, the mean Ca concentration in MO leaves in the present study is the fourth lowest following MO leaf samples collected from Kuje, Nigeria [43], Hawassa, Ethiopia [48] and Jalisco state, Mexico [4], while the mean Zn concentration is the second highest following MO leaves collected from Thailand [49]. Similarly, mean elemental concentrations in MS leaves collected from Ethiopia and Kenya in the current study indicated inconsistent variation when compared with previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Allowing for differences in analytical method and likely inter-study variation in leaf maturity there are many broad similarities. For example, the mean Ca concentration in MO leaves in the present study is the fourth lowest following MO leaf samples collected from Kuje, Nigeria [43], Hawassa, Ethiopia [48] and Jalisco state, Mexico [4], while the mean Zn concentration is the second highest following MO leaves collected from Thailand [49]. Similarly, mean elemental concentrations in MS leaves collected from Ethiopia and Kenya in the current study indicated inconsistent variation when compared with previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…This may be attributed to poor solubility in aqueous medium, poor mechanical property, and instability. 31,32 Further, it has been extensively reported for its application in pharmaceutical and food industry 33,34 as a coating material rather than as polymeric blend additive.…”
Section: Resultsmentioning
confidence: 99%
“…The findings are consistent with those from some previous studies but not others. 16 , 17 The variation may be due to differences in cultivation environments since Moringa is known to absorb heavy metals from environments such as industrial and waste dumps during cultivation. 18 Chronic exposure to arsenic can cause irritation of the stomach and intestines and decreased production of red and white blood cells.…”
Section: Discussionmentioning
confidence: 99%